From muscle to food: oxidative challenges and developmental anomalies in poultry breast muscle. (27th October 2018) - Lilburn, M S; Griffin, J R; Wick, M
ABSTRACT: The glycolytic capacity in the "white muscle fibers" found predominantly in broiler and turkey breast muscle have long been recognized as being key components contributing to optimal pH changes post-harvest and the quality of breast muscle products. The pectoralis major (PMAJ) is the predominant breast muscle and is almost exclusively comprised of fast-twitch glycolytic (anaerobic) type IIb muscle fibers (white). In nature, the pectoralis muscles are designed to meet the intense, periodic energy demands of flight in contrast to the continual, oxidative metabolism (aerobic) inherent to the type I slow twitch fibers (red) in the thigh and drum. Within the past decade, it has been recognized that increased breast muscle yield in modern broiler strains may have contributed to muscle myopathies characterized by visible white striations (white striping; WS) often accompanied by surface hemorrhages and areas of extreme firmness (woody breast; WB). The research to date has primarily addressed differences in muscle physiology and processing characteristics in "normal" and "abnormal" muscle samples from older broilers. One hypothesis is that the extensive accretion of protein in a poorly vascularized breast muscle overwhelms the capacity for coping with excessive production of reactive oxygen species and the term "oxidative stress" has been used to describe this condition. There are few recent reports in poultry, however, which have addressed the potential negative physiological effects imposed by multiple layers of fascia surrounding individual muscle fibers, fiber bundles, and intact muscles on circulation and oxidative stability. The objective of this review is to support our hypothesis that the extensive accretion of breast muscle in a poorly vascularized and tightly bound PMAJ could be creating a "compartment syndrome" like condition leading to the development of the WS and WB anomalies in heavy, high yielding birds. Recent gene expression data support this hypothesis.